An empirical study of the use of neuroscience in sentencing in New South Wales, Australia - Alimardani, Armin (Frontiers in Psychology, 2023)
While neuroscience has been used in Australian courts for the past 40 years, no systematic empirical study has been conducted into how neuroscientific evidence is used in courts. This study provides a systematic review on how neuroscientific evidence is considered in sentencing decisions of New South Wales criminal courts. A comprehensive and systematic search was conducted on three databases. From this search, 331 relevant sentencing decisions before 2016 that discussed neuroscientific evidence were examined. The findings of this study suggest that neuroscientific evidence appeared to contribute to sentencing decisions in less than half of the cases examined; and in the majority of these, it supported a more lenient sentence. 1 Deleted: There is a significant disconnect between how 34 neuroscience evidence is perceived and presented in actual 35 courtrooms, and what scholars seem to think are critical issues … 36 While debates about the potential role of brain scanning and its 37 purported value continue unabated, the practical reality is that 38 brain scan technology is being used in the criminal courtroom, 39 perhaps much more frequently than many observers appreciate 40 (Gaudet and Marchant, 2016a). 1 ¶ 41 There has been increased academic interest in the intersection of 42 neuroscience and law, which has given rise to many scholarly 43 discussions and claims on the use of neuroscientific evidence in 44 courts… 2Similarly, Owen D. Jones and Francis X. Shen summarize the double-edged sword claim in this way, 'a brain too broken may be simply too dangerous to have at large, even if it is somehow less culpable' (emphasis in original):